REVIEW OF THE EXPECTATIONS OF AGED PEOPLE WHO´VE BEEN PART OF THE PROGRAM OF PHISICAL ACTIVITIES OF SESI-PETRÓPOLIS, RIO DE JANEIRO. (Fiep Bulletin - online, 2014)
The target of this study, was to identify the expectations of aged people who've been part of the program of physical activities of SESI-PETRÓPOLIS. The type of research can be known as quanti-qualitative. The samples from this study were composed by (n=40) of, aged people (60 to 79 years), as 2 males and 38 females. The instrument used for the research was a questionary of six closed questions, elaborated and validated exclusively to this study. After each of the aged ones red the questions, they chose one of the best answers for its conditions. The datas obtained from the questionary were tabulated and presented in tables and graphics.  The most relevant results were analyzed through descriptive statistics for the cast of the group. According to the datas earned, the first priority of the participants of the Programa SESI TERCEIRA IDADE, was to get to know people and make new friends, it showed that 82% of the aged ones are not doing well with their social life, 77% of them are unstabled emotionally, 75,8% have a great motivation with the program; 84% made themselves faith full to the program over one year, 25% from the aged ones, had trouble with their health, while 57% seemed in good health but tired and with some body aches; 41% of them are part of the program from medical instructions. The programs called "Programs For the Third Age", even though the different proposals to the audience over 50 or 60 years, has as principal manner the attention to aged not-institutionalized , based on leisure, on occupying the free time and on all the beneath related to physical and psychological health. It's a space where interaction with aged ones make possible the construction of symbolic relationships of identification, where is possible to share the meanings of old age, building new social models of getting old.
Keywords: aged; expectations; physical activities